Le dîner au Latran d'Hadrien II avec les Grecs en 868, sexta feria septuagesimae. Quel jour? Quels préliminaires? - Devos, Paul (Analecta Bollandiana, 1990)
The Vita Hadriani in the Liber pontificalis tells us that Pope Hadrian II, in order to ease tension between the 'Greek' monks in Rome and himself, offered them a banquet at the beginning of his pontificate, sexta feria Septuagesimae, A.D. 868. On what day precisely? Certainly not on 12 February, as is sometimes claimed, but either on 13 or on 20 February. The tension, however, was not so strong as to provoke the monks to commit suicide by hanging.